Thai national telescope studies of ultraluminous X-ray sources - K. Thongpoyai (2020)
© Published under licence by IOP Publishing Ltd. Ultraluminous X-ray sources (ULXs) are extra-galactic, non-nuclear sources with X-ray luminosity in excess of 1039 erg s-1. It has been thought that the majority of ULX populations are stellar-mass objects accreting matter at a super-Eddington rate. Although ULX studies are often focused in the X-ray regime, this work studied the ULXs in the optical regime, identified as the ULX counterparts (CTPs). The optical variability of nine CTPs were observed using the 2.4-m Thai National Telescope. Out of the nine ULXs, we detected three ULXs exhibiting strong variability up to ∼1 magnitude, suggesting that the CTP light does not come from the donor star's emission. The paper discusses the physical origins of the variability which potentially explain the observed light curves.